2010
DOI: 10.1007/s00702-010-0531-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinically available iron chelators induce neuroprotection in the 6-OHDA model of Parkinson’s disease after peripheral administration

Abstract: The iron content of the substantia nigra pars compacta increases in the brains of Parkinson's disease patients. Hence, its removal by iron chelators may retard the progression of the disease. However, information on the ability of clinically available iron chelators to cross the blood brain barrier and be neuroprotective is limited. In this present study three iron chelators, which are currently approved for clinical use, namely the hexadendate, deferrioxamine, the bidentate deferiprone and the tridendate chel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(80 citation statements)
references
References 33 publications
1
77
0
1
Order By: Relevance
“…Animal studies have shown that iron chelators are able to cross the blood brain barrier and are able to remove excess iron from various brain regions in models of brain iron overload 1517 . In early studies, we demonstrated that iron chelators, desferrioxamine, deferasirox and deferiprone, currently in clinical use for treating iron overload in thalassemia major, significantly attenuated SNc dopaminergic neuronal and striatal dopamine loss in the 6-hydroxydopamine PD model, whilst reducing hydroxyl radical formation 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that iron chelators are able to cross the blood brain barrier and are able to remove excess iron from various brain regions in models of brain iron overload 1517 . In early studies, we demonstrated that iron chelators, desferrioxamine, deferasirox and deferiprone, currently in clinical use for treating iron overload in thalassemia major, significantly attenuated SNc dopaminergic neuronal and striatal dopamine loss in the 6-hydroxydopamine PD model, whilst reducing hydroxyl radical formation 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Some iron chelators have been successfully employed in pre-clinical studies of PD. For example, the natural prototype iron chelator/radical scavenger desferrioxamine (Keberle 1964) and the iron-chelating drugs deferiprone and deferasirox were found to be protective against dopaminergic neurodegeneration induced by iron, 6-OHDA, or MPTP (Ben- Shachar et al , 1991Molina-Holgado et al 2008;Dexter et al 2011). The antibiotic metal chelator clioquinol has been shown to inhibit MPTP-induced neurotoxicity in mice (Kaur et al 2003).…”
Section: Ironmentioning
confidence: 98%
“…This therefore represents a suitable animal model to test whether these three chelators are able to cross the BBB and be neuroprotective. In our recent studies [37] we showed that each of these chelators was able to cross the BBB and induce neuroprotection after systemic administration to this animal model. This was exemplified by the preservation of SN dopaminergic cell counts and the normalisation of dopamine metabolism in the striatum.…”
Section: Chelation In Parkinson's Diseasementioning
confidence: 98%